Position of Women in Buddhism: Spiritual and Cultural Activities - Barua, Belu Rani (Arts Faculty Journal, 2012)
The Buddha is a great benefactor of humanity. After the attainment of the Enlightenment in Bodhgaya and preaching First Sermon in Sarnath, the Buddha founded the order of Monks (Bhikkhusangha). This order of Monks increased and within forty five years of Buddhas ministry it had spread throughout ancient India. But groundless belief of Brahmins is that woman is inferior to man. The position which the woman lost under the dominance of the Brahmins of the day evidently showed little sympathy for her. In this article I will explore the position of women considering their spiritual and cultural activities. DOI: http://dx.doi.org/10.3329/afj.v4i0.12933 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.75-84